Journal de campagne - Gitai, Amos; Aviv, Nurith (Amos Gitai, 2003)
After facing all sorts of daunting obstacles put in his way by Israeli soldiers, officers and authorities, who did everything they could to stop shooting the film, Amos Gitai eventually managed to finish this documentary on location in the West Bank and the Gaza Strip, territories occupied by Israel since Lebanon’s invasion. It is a compelling and poignant portrait of everyday life in those occupied areas that depicts from crowded buses and the busy activities of markets and farms to comments by Israeli soldiers, most of whom support the occupation - except for one who suggests the land should be handed back to the Palestinians. The director also gives voice to Palestinians and Jewish settlers. The highlight of this documentary is an interview with the mayor, who became paralytic after a bomb blast. On the whole, the film is a generous effort to present a broad overview of Palestinians’ and Jews’ daily life in these bitterly disputed territories. When it was first made for Israeli TV, the film was banned as the country’s censors did not allow such an open discussion on Israel’s crucial issues to be aired. [38.mostra.org]